Iron‐Catalyzed Wacker‐type Oxidation of Olefins at Room Temperature with 1, 3‐Diketones or Neocuproine as Ligands. (14th May 2021) - Puls, Florian; Linke, Philipp; Kataeva, Olga; Knölker, Hans‐Joachim
Abstract: Herein, we describe a convenient and general method for the oxidation of olefins to ketones using either tris(dibenzoylmethanato)iron(III) [Fe(dbm)3 ] or a combination of iron(II) chloride and neocuproine (2, 9‐dimethyl‐1, 10‐phenanthroline) as catalysts and phenylsilane (PhSiH3 ) as additive. All reactions proceed efficiently at room temperature using air as sole oxidant. This transformation has been applied to a variety of substrates, is operationally simple, proceeds under mild reaction conditions, and shows a high functional‐group tolerance. The ketones are formed smoothly in up to 97 % yield and with 100 % regioselectivity, while the corresponding alcohols were observed as by‐products. Labeling experiments showed that an incorporated hydrogen atom originates from the phenylsilane. The oxygen atom of the ketone as well as of the alcohol derives from the ambient atmosphere. Abstract : Various iron catalyst systems featuring a range of different ligands have been evaluated for the Wacker‐type oxidation of olefins to ketones in the presence of phenylsilane at room temperature and ambient air. The transformation is operationally simple, sustainable, exhibits a high functional group tolerance, and is applicable to natural product synthesis.